Interview with a true green giant - Crumm, David, author; David Crumm Media, publisher (Colorado State University. Libraries, 2009)
Rolston is a true "green giant," urging the kinds of experience people all need to share, if humans are to survive as a species. He is working to knit together a rather unlikely community of secular scientists, nature lovers, public policy experts, and people of faith. Rolston claims to do his best teaching by sneaking up on people and inviting them to get in a whole lot deeper than they previously thought possible. He is something of a mixture of Charles Darwin, the Dalai Llama, Al Gore, and Billy Graham.
Includes Part 1: Holmes Rolston and ecology's secret story; and Part 2: Holmes Rolston and the power of Psalms.
Keywords: biography; environmental ethics; Rolston, Holmes, 1932-2025; science; religion